Oxygen sensing behaviors of Eu (Ba1-xPrx)2Cu3O7-δ and Eu1-yPrBa2Cu3O7-δ ceramic rods with hot-spot / Ikhwan Adzam - Adzam, Mohd Ikhwan (2015)
Oxygen sensing properties of Pr doped EuBa2Cu307-c5 short ceramic rods were investigated. The Eu(Bai-xPrx)zCu307-o (x=O, 0.05, 0.25 and x=0.40) and EuiyPryBa2Cu307- a (y=O, 0.05, 0.1 0, 0.15 and y=0.20) rods with dimensions of around 13mm x 0.65mm x 0.65mm and 13mm x 1.48mm x 1.48mm, respectively were prepared by standard solid state reaction method. For the first series of this study, Eu(Ba1-xPrxhCu307_0 rods were prepared to investigate the influences of changes in structure and the expected decrease in average Cu valence on oxygen sensing properties. X-ray powder diffraction analysis showed that orthorhombicity of the structure reduces with increasing Pr concentration. After the hot-spot became visible, samples x=O and x=0.05 showed a sudden drop in current before remaining constant with increasing voltage. This is suggested to be due to steep increase in resistivity caused by the sudden increase in temperature of the hot-spot together with the structural changes that lead to reduction in oxygen content. However, for the x=0.25 and x=0.4 rods the output current shows no sudden drop. The results also showed that the reduced magnitude of the output current with increasing Pr could be attributed to the reduction in intrinsic hole concentration. The output current for all samples showed strong dependence on p02. Although the sensitivity of the output current to p02 between 50% p02 and 100% p02 reduces with increasing x, the stability and repeatability of the output current seems to improve. Also, while Pr doped Eu(BaixPrx) 2Cu307_0 reduces the magnitude of the output current, it produces better response time towards different p02. On the other hand, Eui-yPryBazCu307-a rods were prepared and X-Ray powder diffraction analysis showed that, Pr doped Eu1-yPryBazCu307-o were all orthorhombic in unit cell structure with reduction in orthorhombicity upon doping. The /-V curve showed a relatively constant output current after the appearance of hot-spot. Meanwhile, the magnitude of the constant output current was observed to be decreasing with increasing Pr doping which indicates possible reduction in intrinsic hole concentration. In addition, the output current for rods with y=O.O, 0.05 and 0.10 showed a sudden drop upon the appearance of hot-spot, due to the sudden increase in hot-spot temperature, before becoming slightly constant. However, the sudden drop of output current upon appearance of hot-spot was not observed when Pr was increased to y=0.15 and 0.20 but instead a stable output current was observed. Interestingly, the output current after appearance of hot-spot for all rods showed strong dependency on ambient oxygen concentration. The sensitivity for each rod however, reduces with increasing ambient oxygen concentration. Pr doped Eui-yPryBazCu307_0 seems to prevent the sensitivity from dropping to almost zero as was the case of Eu(Ba1_ yPry)2Cu30 7_0 rods due to existence of Cu-0 chains in the orthorhombic structure. Pr doping (for y=O.lO) has also resulted in better oxygen absorption response time and better output current stability compared to other rods.